2019
DOI: 10.1186/s41747-019-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric quantitative and texture 18F-FDG PET/CT analysis for primary malignant tumour grade differentiation

Abstract: Background18F-FDG positron emission tomography/computed tomography (PET/CT) is a successfully used imaging modality in oncology. The aim of the study was to investigate a connection of epithelial tumour differentiation grade with both semiquantitative and quantitative metabolic PET data focusing on creation of multiparametric model of tumour grade prediction utilising both standardised uptake value-based and texture-based 18F-FDG PET parameters and to investigate an influence of different image segmentation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We collected 19 publications focusing on gynecological cancers [ 82 , 104 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ], particularly on cervical (74%), endometrial (16%), epithelial (5%) and vulvar cancer (5%). The average number of patients was 93 (median = 84, range, 20–190).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected 19 publications focusing on gynecological cancers [ 82 , 104 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ], particularly on cervical (74%), endometrial (16%), epithelial (5%) and vulvar cancer (5%). The average number of patients was 93 (median = 84, range, 20–190).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar work, Shen et al [ 212 ] concluded that homogeneity from the GLCM combined with TLG was the best combination of predictors, partially supporting these results. In a study involving 84 patients, Novikov [ 221 ] evaluated whether PET radiomic features of epithelial tumors would be able to predict the differentiation grade, reporting an accuracy between 91% and 100%. Finally, regarding prognosis, Lucia et al [ 223 ] presented one of a very few papers aiming at validating a previously developed radiomics model [ 222 ], providing compelling evidence of the ability of PET+MR radiomics to predict disease-free survival and locoregional control in locally advanced cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of classical GMDH in the modeling of nonlinear problems has been demonstrated in various studies [33][34][35][36]. However, along with its advantages, it possesses the following limitations: (i) second-order polynomials, (ii) only two inputs for each neuron, (iii) inputs of each neuron can only be selected from the adjacent layer [37,38].…”
Section: Generalized Structure Of Group Methods Of Data Handling (Gmdh)mentioning
confidence: 99%
“…Another cohort revealed that distant metastasis was signi cantly associated with greater average tumor volume [38]. Although no study has reported a relationship between compacity and prognosis in cervical cancer, few studies have shown that compacity is associated with several tumor types, including pelvic malignancies [39][40][41].…”
Section: Representative Casesmentioning
confidence: 99%